Irrigation, Nutrition, and Citrus Fruit Quality - Mongi Zekri; Tom A. Obreza; Robert Koo (EDIS, 2003)
The effects of irrigation and nutrition on fruit quality are important and should be understood and taken into consideration by citrus growers and production managers to increase profitability and enhance sustainability and worldwide competitiveness. This document is SL 207, a fact sheet of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First printed: April 2003.